2005
DOI: 10.1136/bmj.38498.669595.8f
|View full text |Cite
|
Sign up to set email alerts
|

Selective chromosome analysis in couples with two or more miscarriages: case-control study

Abstract: Objective To identify additional factors, such as maternal age or factors related to previous reproductive outcome or family history, and the corresponding probability of carrying a chromosome abnormality in couples with two or more miscarriages. Design Nested case-control study. Setting Six centres for clinical genetics in the Netherlands. Participants Couples referred for chromosome analysis after two or more miscarriages in 1992-2000; 279 carrier couples were marked as cases, and 428 non-carrier couples ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
2
16

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(95 citation statements)
references
References 15 publications
(12 reference statements)
2
75
2
16
Order By: Relevance
“…The reproductive outcomes of the 18 carriers are shown in Table 3 in RPL couples was 5.04%. Previous studies have reported the incidence of these abnormalities and polymorphisms at 3-6% (Tharapel et al, 1985;De Braekeleeret and Dao, 1990;Clifford et al, 1994;Franssen et al, 2005). Among the 2720 RPL couples, 2.24% of carriers had chromosome abnormalities and 2.80% had polymorphisms.…”
Section: Resultsmentioning
confidence: 99%
“…The reproductive outcomes of the 18 carriers are shown in Table 3 in RPL couples was 5.04%. Previous studies have reported the incidence of these abnormalities and polymorphisms at 3-6% (Tharapel et al, 1985;De Braekeleeret and Dao, 1990;Clifford et al, 1994;Franssen et al, 2005). Among the 2720 RPL couples, 2.24% of carriers had chromosome abnormalities and 2.80% had polymorphisms.…”
Section: Resultsmentioning
confidence: 99%
“…RM is a highly heterogenic condition; to strive for more homogeneity, in the present study we only included women who had their third consecutive miscarriage below the age of 31. A younger age at diagnosis makes a maternal cause of RM more plausible and reduces the chance of miscarriages due to fetal abnormalities 30. Another strength is the availability of a wide range of covariates in both groups (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the incidence of chromosomal abnormalities is higher in women than in men (11,16), possibly because abnormalities compatible with fertility in females may be associated with sterility in males (9,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Such balanced translocations account for the largest percentage of karyotypic abnormalities (9). The clinical consequences of such abnormal gametes include repeated abortions, stillbirth, and birth of malformed children and mentally handicapped children (10).…”
Section: Discussionmentioning
confidence: 99%